VecLI: A framework for calculating vector landscape indices considering landscape fragmentation. (March 2022) - Yao, Yao; Cheng, Tao; Sun, Zhenhui; Li, Linlong; Chen, Dongsheng; Chen, Ziheng; Wei, Jianglin; Guan, Qingfeng
Abstract: Currently, raster-based landscape indices (LIs) that measures the landscape pattern of raster-format land-use data, can be easily computed by relevant software (e.g., Fragstats). Unfortunately, open-access software for vector-based LIs often implement a small variety of metrics, which cannot meet the growing demand of the GIS and landscape design research. The common approach often results in a loss of accuracy. Hence, this paper presents the state-of-the-art VecLI framework for computing 217 vector-based LIs. A parcel merging algorithm is proposed to address the impact of landscape fragmentation on vector-based LIs by considering the neighborhood effect. A case study was conduct in Shunde, China. The result shows that 80% of the LIs from VecLI are strongly correlated to Fragstats's LIs. The patch perimeter-related metrics from VecLI portray a more realistic geographical pattern compared to those from Fragstats. Moreover, the VecLI-based software is developed for use by the GIS and landscape design researchers. Highlights: A new unifying computational framework for vector-based landscape indices is proposed. 79.3% of the VecLI metrics are strongly correlated to the raster-based indices of Fragstats. A parcel-merging algorithm is proposed to effectively address the impact of landscape fragmentation. The open-access VecLI software based on the proposed framework has been developed and released.